Navigating the Interplay of Profitability, Debt Policy, and Dividend Strategy in Business Valuation - Kuswandi, Engkus (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
Dividend policy is often considered a good signal for investors in assessing the good and bad of the company, the increase and decrease of the Dividend Policy contains information on the current state of company management and the state of profits in the future. This study was conducted to determine and analyze the Effect of Profitability and Debt Policy on Company Value with Dividend Policy as an Intervening Variable. This study was conducted using associative quantitative methods. The number of samples in this study based on criteria was obtained as many as 112 data from 16 companies for 7 periods with the Eviews 11 testing tool. The analysis techniques used are descriptive statistical analysis, panel data regression testing, classical assumption testing, and path analysis. Next, hypothesis testing using f test, t test and coefficient of determination assisted by using Eviews 11 program. The results showed simultaneous tests that profitability, debt policy and dividend policy had a significant effect on the value of the company. The results of the track test show that dividend policy is able to mediate the relationship between profitability and debt policy to company value.